2009
DOI: 10.1007/bf03346609
|View full text |Cite
|
Sign up to set email alerts
|

Elevated circulating free fatty acids levels causing pancreatic islet cell dysfunction through oxidative stress

Abstract: Elevated circulating FFA levels may contribute to causing the abnormalities of pancreatic islet cell function through active oxidative stress and oxidative stress-sensitive signaling pathway, which may play a key role in the development of impaired insulin secretion seen in obese Type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
2
11
0
1
Order By: Relevance
“…We have demonstrated previously that 1) prolonged elevation of plasma FFA in rats impairs glucose-stimulated insulin secretion (GSIS) in vivo during hyperglycemic clamps and ex vivo in freshly isolated islets and 2) the treatment with the antioxidants N-acetylcysteine, taurine, or tempol, which decreases islet ROS measured with dihydrodichlorofluorescein diacetate (H 2 DCF-DA), prevents the impairing effects of FFA on ␤-cell function (51). Zhang et al (72) confirmed our findings in rats (51) in a different model of prolonged FFA elevation. Our group has also shown that the antioxidant taurine alleviates FFA-induced impairment in ␤-cell function in humans (68).…”
supporting
confidence: 81%
“…We have demonstrated previously that 1) prolonged elevation of plasma FFA in rats impairs glucose-stimulated insulin secretion (GSIS) in vivo during hyperglycemic clamps and ex vivo in freshly isolated islets and 2) the treatment with the antioxidants N-acetylcysteine, taurine, or tempol, which decreases islet ROS measured with dihydrodichlorofluorescein diacetate (H 2 DCF-DA), prevents the impairing effects of FFA on ␤-cell function (51). Zhang et al (72) confirmed our findings in rats (51) in a different model of prolonged FFA elevation. Our group has also shown that the antioxidant taurine alleviates FFA-induced impairment in ␤-cell function in humans (68).…”
supporting
confidence: 81%
“…Support for a role of PKC is from (38,76). Support for a role of oxidative stress is from (63,93,97) and for ER stress from our studies in humans (91). Support for a role of inflammation is from (29,65,75,88) and from our studies using salicylate in rats (unpublished observartions).…”
Section: Mechanisms Of Lipid-induced ␤-Cell Dysfunction and Death: Fomentioning
confidence: 68%
“…We found that the antioxidants taurine, N-acetylcysteine (NAC), and tempol prevented the impairment in ␤-cell function induced by prolonged exposure to FFA in vivo during hyperglycemic clamps and ex vivo in isolated islets of oleate-treated rats (63). Other authors have found NAC to prevent impairment of GSIS in vivo and in the perfused pancreas of 96-h Intralipid-infused rats (97).…”
Section: Mechanisms Of Lipid-induced ␤-Cell Dysfunction and Death: Fomentioning
confidence: 88%
“…9 Underlying mechanisms include lipid accumulation with subsequent inflammation, 10 oxidative stress, 11 lipid peroxidation, 12 and endoplasmic reticulum stress. 13 HDL may protect against β-cell dysfunction and increase glucose-stimulated insulin secretion (GSIS) via cellular cholesterol removal 2,4,[14][15][16] and direct signaling actions.…”
mentioning
confidence: 99%